Determination of critical factors and the best alternatives for developing biodiesel from Maggot BSF - Rimantho, Dino; Pratomo, Vector Anggit; Pane, Erlanda Augupta; Noywuli, Nicolaus (SINERGI, 2026)
This paper explores the approach for producing biodiesel from Maggot Black Soldier Fly (BSF) as a sustainable renewable energy source in Indonesia. The SWOT and VIKOR techniques determine the most effective strategy for promoting renewable energy in Indonesia. The paper included numerous respondents to ascertain the criteria and assess each option. Environmental consciousness is an important strong component in biodiesel development, with a value of 1.52. A significant drawback in biodiesel production is the elevated investment costs, quantified at 1.48. A notable opportunity in biodiesel development is its potential as an environmentally sustainable energy alternative, scoring 1.32, while a considerable threat is inadequate financial assistance, scoring 1.24. Moreover, applying the VIKOR approach reveals that alternative 6 (Enhancing collaboration among stakeholders) is the most critical option, as expert evaluations indicate, with a value of 0.048. The outcomes of this study require enhancement since additional research is necessary to yield more precise findings that will augment our comprehension of the evolution of renewable energy in Indonesia. Future studies should focus on the ramifications of producing biodiesel from BSF maggots, particularly in terms of energy security and energy autonomy in Indonesia.